2016
DOI: 10.1002/rcm.7787
|View full text |Cite
|
Sign up to set email alerts
|

Mineral mediated isotope fractionation of soil water

Abstract: The isotopic signature of soil water is influenced by mineral-water interaction. During the hydration of clay, different minerals deplete free water in heavy isotopes. The extracted soil water (dehydration water) gathered from clay-rich soils is generally more depleted in the heavy isotopes than the spike water, making results obtained for different soil types difficult to compare. Isotope effects observed at the mineral-water interface highlight potential explanations for eco-hydrological separation of water … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
96
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(110 citation statements)
references
References 41 publications
(58 reference statements)
11
96
3
Order By: Relevance
“…This equation can be rearranged to calculate the amount of soil water (Equation ) and the isotopic composition of soil water (Equation ), respectively: amountsoil water=amountMix×italici.italicc.Mixamountspike×italici.italicc.spikeitalici.italicc.soil water italici.italicc.soil water=amountMix×italici.italicc.Mixamountspike×italici.italicc.spikeitalicamount.soil water Underlying the above calculation is the approximation that the water remaining in the soil after oven drying has the same isotopic composition as the water extracted from fresh soil, an assumption which is expected to be false, but necessary, as no other better information on its isotopic composition is available. Due to this approximation, the result of this calculation is not precise.…”
Section: Methodssupporting
confidence: 92%
See 1 more Smart Citation
“…This equation can be rearranged to calculate the amount of soil water (Equation ) and the isotopic composition of soil water (Equation ), respectively: amountsoil water=amountMix×italici.italicc.Mixamountspike×italici.italicc.spikeitalici.italicc.soil water italici.italicc.soil water=amountMix×italici.italicc.Mixamountspike×italici.italicc.spikeitalicamount.soil water Underlying the above calculation is the approximation that the water remaining in the soil after oven drying has the same isotopic composition as the water extracted from fresh soil, an assumption which is expected to be false, but necessary, as no other better information on its isotopic composition is available. Due to this approximation, the result of this calculation is not precise.…”
Section: Methodssupporting
confidence: 92%
“…It is unclear whether the exchange effect is in fact only due to exchange with residual soil water, or perhaps also due to exchange with the soil matrix (clay minerals, organic matter). Our results indicate that the amount of exchange is different for O and H which would indicate that matrix effects (which always only act for one element) are in play.…”
Section: Discussionmentioning
confidence: 99%
“…This accordance indicates that δ soil reflected water pools available for RWU for a wide range of Ψ. Additionally, δ soil below 20 cm depth and deionised water used for initial saturation agreed well before phase II. Therefore, no measurable tension‐ and texture‐mediated isotopic effect (Orlowski et al , , ; Gaj et al , ) was found in this study. For the soil used in the present experiment, this also contradicts the recently controversially discussed hypothesis of two water worlds (McDonnell, ) that explains observed differences between plant and stream water isotopic compositions by conceptualising the co‐existence of two isotopically distinct water pools, one available for RWU and one available for soil water flow.…”
Section: Resultscontrasting
confidence: 55%
“…These effects include water isotopologue organization and partitioning at interfaces with organic material adsorbed to soil particle surfaces (Chen, Auerswald, & Schnyder, 2016), or around cations adsorbed to the clay particle surfaces (Oerter et al, 2014), or by the soil mineral particles themselves (Gaj et al, 2017). These effects include water isotopologue organization and partitioning at interfaces with organic material adsorbed to soil particle surfaces (Chen, Auerswald, & Schnyder, 2016), or around cations adsorbed to the clay particle surfaces (Oerter et al, 2014), or by the soil mineral particles themselves (Gaj et al, 2017).…”
Section: Soil and Xylem Water δ 2 H And δ 18 O Valuesmentioning
confidence: 99%